Ramelteon ameliorated 1-methyl-4-phenylpyridinium (MPP+)-induced neurotoxicity in neuronal cells in a mitochondrial-dependent pathway. Issue 1 (1st January 2021) - Li, Chuo; Zhang, Yusheng; Liu, Rongrong; Mai, Yuzhen
ABSTRACT: Parkinson's disease (PD) is a common neurodegenerative disease with global health and economic impact. 1-methyl-4-phenylpyridinium (MPP+)-induced mitochondrial dysfunction and oxidative stress are reported to participate in the pathological mechanism of PD. Ramelteon is a novel oral hypnotic agent that has recently been reported to display neuronal protective effects. However, it is unknown whether Ramelteon possesses a beneficial effect in PD. In this study, we aimed to examine the potential function of Ramelteon in MPP+-challenged neurons. We found that Ramelteon rescued the cell viability reduced by MPP+-stimulation. Further, oxidative stress in MPP+-challenged SH-SY5Y cells was mitigated by Ramelteon as verified by the upregulated levels of mitochondrial reactive oxygen species (ROS) and protein carboxyl, and the upregulation of NADPH oxidase 4 (NOX-4). Furthermore, the declined mitochondrial membrane potential (Δ Ψm ) caused by MPP+ was reversed by Ramelteon. Importantly, Ramelteon attenuated MPP+-induced apoptosis, accompanied by a decreased ratio of Bax/Bcl-2, inhibition of cytochrome C release, and downregulation of cleaved caspase-3. For the first time, we conclude that Ramelteon might ameliorate MPP+-induced neurotoxicity in neuronal cells in a mitochondrial-dependent pathway.